An analysis of risk factors for incomplete immunization for children in Côte d’Ivoire: Examination of 1998-1999 and 2011-2012 demographic and health survey - Douba, Alfred; Aka Lepri Bernadin, Nicaise; Attoh-Toure, Harvey; Bangaman Akani, Christian; Yao, Gnissan Henry Auguste; Konan, N’guessan; Accray-Zengbe, Petronille (HEALTH SCIENCES AND DISEASE, 2016)
In 2012, the global number of children who did not receive the third dose of Diphtheria, Pertussis and Tetanus vaccine was estimated to 22.6 million. Factors associated with immunization status among children in Côte d’Ivoire were examined in order to determine the trends of these factors and inform health policy makers. The study was a retrospective one using 1998-1999 and 2011-2012 Côte d’Ivoire Demography and Health Surveys data. The sample included 3878 children aged 12 to 59 months representing 1326 children from 1998-1999 data, and 2552 children from the 2011-2012 data. The outcome variable was vaccination status defined as “not fully immunized”. A child defined as not fully immunized if he/she did not received at least one of the following vaccines: BCG, the third dose of pentavalent, the third dose of polio, and measles vaccine. Data was analyzed using SPSS. Chi-square test was computed and Spearman correlation analysis were used to describe the sample. Univariate analysis, and multivariate analysis using logistic regression were performed to unclose the factors. Findings showed that not fully immunized children increased significantly (P<0.0001) from 1998-1999 (41.9%) to 2011-2012 (48.9%). Children who did not received BCG, DPT3, polio3 and measles vaccine increased significantly from 1998-1999 to 2011-2012. Child birth place (adjusted OR = 2.57, CI95=1.96, 3.37), media access (adj. OR = 1.82, CI95=1.38, 2.38), literacy (adj. OR = 1.95, CI95 = 1.19, 3.20), place of residence (adj. OR = 1.38, CI95 = 1.04, 1.83), and religion (adj. OR = 1.89, CI95 = 1.28, 2.79) were associated with odds of not being fully immunized in 1998-1999 as well as in 2011-2012. Health officials should take into account these factors in immunization strategies and policy making in Côte d’Ivoire.